Last Words : Variations on a Theme in Cultural History - Guthke, Karl S. (Book collections on Project MUSE., 2001)
Whether Goethe actually cried "More light!" on his deathbed, or whether Conrad Hilton checked out of this world after uttering "Leave the shower curtain on the inside of the tub," last words, regardless of authenticity, have long captured the imagination of Western society. In this playfully serious investigation based on factual accounts, anecdotes, literary works, and films, Karl Guthke explores the cultural importance of those words spoken at the border between this world and the next. The exit lines of both famous and ordinary people embody for us a sense of drama and truthfulness and reve.